Gambaran Citra Tubuh pada Member Gym Black Diamond Kupang - Zefanya M.I. Bengu; Feronika Ratu; Shela Christine Pello (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2026)
Body image is an individual’s perception, evaluation, and feelings toward their physical appearance, whether positive or negative. This study was motivated by the increasing public attention to physical appearance and the ideal body shape, which may influence self-confidence and psychological well-being. The purpose of this study was to describe the body image of members of Black Diamond Gym. This study employed a quantitative method with a descriptive approach. The participants consisted of 136 members of Black Diamond Gym Kupang selected through simple random sampling techniques. Data were collected using a body image scale developed based on aspects of body image. Data analysis was conducted using descriptive statistical tests with IBM SPSS Statistics 26. The results showed that the majority of respondents were in the moderate category of body image. Based on gender, both male and female participants were predominantly in the moderate category. These findings indicate that most gym members had relatively positive perceptions of their bodies, although some individuals still experienced dissatisfaction with their physical condition. In addition, gym activities contributed positively to improving self-confidence, physical health, and mental health.